2010
DOI: 10.1186/1476-9255-7-1
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways involved in LPS induced TNFalpha production in human adipocytes

Abstract: BackgroundThe development of obesity has been linked to an inflammatory process, and the role of adipose tissue in the secretion of pro-inflammatory molecules such as IL-6 or TNFalpha has now been largely confirmed. Although TNFalpha secretion by adipose cells is probably induced, most notably by TLR ligands, the activation and secretion pathways of this cytokine are not yet entirely understood. Moreover, given that macrophagic infiltration is a characteristic of obesity, it is difficult to clearly establish t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 40 publications
5
75
0
1
Order By: Relevance
“…These inhibitors have no intrinsic effects on cell death and IL-6 secretion (data not shown) and were previously controlled for their efficiency. 7 A strong and significant inhibition of HMGB1-induced IL-6 secretion was shown when NF-kB and P38 MAPK inhibitors were co-incubating with HMGB1, which indicates the involvement of NF-kB and P38 MAPK in the disulfide HMGB1 signaling (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…These inhibitors have no intrinsic effects on cell death and IL-6 secretion (data not shown) and were previously controlled for their efficiency. 7 A strong and significant inhibition of HMGB1-induced IL-6 secretion was shown when NF-kB and P38 MAPK inhibitors were co-incubating with HMGB1, which indicates the involvement of NF-kB and P38 MAPK in the disulfide HMGB1 signaling (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…We speculate that TNF-a production may not solely be dependent on the NF-jB mediated pathway; there may be other pathway(s) that can also regulate TNF-a production. Indeed, Hoareau et al 71 showed that both NF-jB and the p38 MAP Kinase pathway could be involved in TNF-a secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mammalian receptors for LPS have been identified such as b 2 -integrins CD11/CD18, the macrophage scavenger receptor for acetylated LDL, L-selectin and the most important CD14. LPS activates a number of intracellular signaling pathways, including IkB kinase-nuclear factor kB (NFkB) pathway and three mitogen-activated protein kinase pathways [16,17] . These pathways phosphorylate and activate various transcription factors, including NFkB/Rel proteins, activator protein 1 (AP-1) and nuclear factor-IL-6 (NF-IL6).…”
Section: Cell Signaling Networkmentioning
confidence: 99%